Effectiveness of a Supportive-Educative Nursing System Program on Knowledge and Maternal Behavior in Care for Children with Post-COVID-19 at Home - Sanongyard, Jaruwan; Siratirakul, Lakana; Hemtanon, Sutat; Thammakijpirote, Khunruethai (Journal of Phrapokklao Nursing College, Chanthaburi, 2024)
This quasi-experimental research aimed to examine the effectiveness of a supportive-educative nursing system program on knowledge and maternal behavior in care for children with post-COVID-19 at home. The samples were 80 mothers caring for children with post-COVID-19 at home and were equally divided into an experimental group (n = 40) and a control group (n = 40). The research instruments included a supportive-educative nursing system program, a general information questionnaire, a maternal knowledge in care for children with post-COVID-19 at home assessment form with a reliability of .79, and a maternal behavior in care for children with post-COVID-19 at home measurement form with a reliability of .84. The implementation and data collection were conducted from January to August 2023. Data were analyzed using frequency, percentage, paired t-test, and independent t-test. The research results revealed that 1) after the experiment, the experimental group had statistically significantly higher mean scores of knowledge in care for children with post-COVID-19 at home and behavior in care for children with post-COVID-19 at home than those of before the experiment (t = 5.298, p < .001 and t = 15.325, p < .001, respectively); and 2) after the experiment, the experimental group had statistically significantly higher mean scores of knowledge in care for children with post-COVID-19 at home and behavior in care for children with post-COVID-19 at home than those of the control group (t = 4.688, p < .001 and t = 14.176, p < .001, respectively). This research suggests that nurses should utilize this supportive-educative nursing system program for mothers caring for children with post-COVID-19 at home. This will help mothers improve their knowledge and behavior in care for the children.